Liberal arts online: A Thai College's response to the COVID-19 pandemic - Alexander Nanni (2022)
The COVID-19 pandemic has spurred a rapid transition to online teaching and learning. This research investigates the impact of the pandemic on a liberal arts college in Thailand. Data was gathered via email correspondence and interviews with executives at the college. The texts of the exchanges were analyzed using a general inductive approach, and the findings were triangulated with relevant documents. The analysis yielded a series of first-order themes, which centered on the four second-order themes of actively engaging through technology, facing hardship, rebalancing, and education globally. The findings of this research contribute to the body of knowledge on liberal arts, online education, crisis management in higher education, and emergency remote teaching (ERT), providing a snapshot of the college's reaction to a highly complex and evolving situation. This article will be of interest to practitioners and researchers who wish to compare the responses of the college to those of other similar institutions in Southeast Asia, East Asia, and beyond.